2012
DOI: 10.1016/j.nano.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface modification favors benign biofilm formation and impedes adherence by pathogens

Abstract: We have found in vitro that a biofilm of benign Escherichia coli 83972 interferes with urinary catheter colonization by pathogens, and in human studies E. coli 83972-coated urinary catheters are associated with lower rates of catheter-associated urinary tract infections. We hypothesized that modifying surfaces to present mannose ligands for the type 1 fimbriae of E. coli would promote formation of dense E. coli 83972 biofilms, thereby interfering with surface colonizaion by Enterococcus faecalis, a common urop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…These devices are often colonized by single bacterial species like Escherichia coli [5]. E. coli is responsible for 80% of the urinary tract infections and it was observed that even after antibiotic therapy it can persist and re-emerge in the bladder and in associated urinary tract biomedical devices (eg urinary catheters) [3,6,7]. E. coli has also been found in breast implants, being responsible for 1.5% of associated infections, and contact lenses [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…These devices are often colonized by single bacterial species like Escherichia coli [5]. E. coli is responsible for 80% of the urinary tract infections and it was observed that even after antibiotic therapy it can persist and re-emerge in the bladder and in associated urinary tract biomedical devices (eg urinary catheters) [3,6,7]. E. coli has also been found in breast implants, being responsible for 1.5% of associated infections, and contact lenses [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…microbial adhesion | structured surfaces | bacterial appendages | surface texture | surface wetting T he attachment of bacteria to solid surfaces is the first step in the formation of biofilms-communities of sessile microbes surrounded by a polymeric matrix (1,2). A growing appreciation of the ubiquity and importance of biofilms in medicine and industry has led to a proliferation of antiadhesion strategies that include chemical, biological, and physical approaches (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Attempts to block biofilm formation must also take into account the rapid evolution of bacteria and their ability to resist many chemical assaults (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Two Spanish studies have suggested a low prevalence of the clone amongst poultry and pig farms in that nation. [208,209] Mora found that the clone comprised 1.5% of E. coli strains recovered from Spanish poultry between 2007 and 2009. Surprisingly, in this study, the prevalence amongst E. coli recovered from retail chicken meat was considerably higher, comprising 7% of strains.…”
Section: The Americasmentioning
confidence: 99%
“…[209] The high similarity of an isolate from raw chicken and two human infections in the same geographical region in Canada was suggestive of transmission from foodstuff to humans. [190] Although these links are tantalising, there remains to be found a solid molecular epidemiologic connection between human infection and prior consumption of food containing ST131 E. coli.…”
Section: The Americasmentioning
confidence: 99%
See 1 more Smart Citation